Understanding the physiological and molecular aspects of charcoal rot resistance mechanisms in sorghum and soybean - Noor, Afsana (Kansas State University, 2022)
Charcoal rot (CR) of soybean (Glycine max (L.) Merr.) and sorghum (Sorghum bicolor (L.) Moench) is caused by the hemibiotrophic soilborne fungus Macrophomina phaseolina (MP) and is an important pathogen in the midwestern United States. Complex molecular mechanisms underlie the interaction of MP with these two hosts, which impedes resistance breeding. To select for charcoal rot resistance, a thorough understanding of the host’s physiological and molecular responses to MP along with screening of genotypes with resistance to CR is essential. To understand MP induced host’s physiological and molecular responses, first we investigated MP-induced oxidative stress-mediated senescence by using the reactive oxygen species (ROS) scavenger ascorbic acid in soybean seedlings. Three soybean isolates of MP were tested for their sensitivity to ascorbic acid using an in-vitro assay. An in-planta soybean cut-stem assay was used for the exogenous application of ascorbic acid (oxidized and reduced form) following inoculation with MP. A ROS (H₂O₂) quantification assay was used to validate H₂O₂ induced by MP and ascorbic acid pre-treatment. All three MP isolates were sensitive to ascorbic acid concentrations of ≥ 15 mM. Ascorbic acid (10mM) pre-treatment following MP inoculation reduced CR lesion length compared to inoculated treatment. MP induced a significantly higher H₂O₂ than ascorbic acid pre-treated inoculated plant. Second, through comparative transcriptomics, MP-resistant and susceptible soybean genotypes revealed contrasted responses to MP-induced senescence. Gene Ontology and pathway analysis showed MP-induced receptor kinase like genes in both genotypes while down-regulated defense related antioxidant, hormonal, and other metabolic pathways in both genotypes. Ascorbic acid pre-treatment induced a more significant number of photosynthesis genes in both genotypes. Hydrogen peroxide pre-treatment following inoculation showed up-regulation of oxidative stress responsive pathways while down-regulated photosynthesis and hormonal signal transduction pathways. Third, the NAM phenotyping for CR resistance results of location- and year-wise data showed strong genotype by environment interactions. Overall, using MP screening, charcoal rot resistance phenotyping in the NAM parental lines revealed the genotype SC1103 as the most resistant line and Segaolane and Macia as the most susceptible. The SC1103 NAM family-derived population can be used for charcoal rot resistance in association studies to map charcoal rot resistance.
Keywords: Charcoal rot; Macrophomina phaseolina; Oxidative stress; Ascorbic acid; Sorghum NAM population; NAM phenotyping